Attis, between myth and history : king, priest, and God - Lancellotti, Maria Grazia. (Religions in the Graeco-Roman World, 2002)
This volume deals with the figure of Attis. The work aims to reconsider the mythical and cultic information about this character, trying to provide proof of the processes of \'construction\' and \'reconstruction\' that have contributed to the moulding of the different forms of Attis that developed as a result of various demands within different religious traditions. After an introduction about the history of the studies, the first part examines the oldest evidence on Attis, resorting to comparison with religious traditions earlier than or contemporary with Phrygian culture. The second part tackles the classical world and collects the elements of continuity and of innovation in respect of Asianic religious traditions. The third part analyses the problem of the processes of reinterpretation of the traditional cults that both the \'pagan\' philosophers and the fathers of the Church effected. The link between Attis and Death is discussed in the fourth part.